KONSEP MANAJEMEN PERPUSTAKAAN DALAM MENINGKATKAN MINAT BACA SISWA DI MTs NEGERI 1 PURWOREJO - rosa sugesti; Shofa Aulia Kumala (Institut Agama Islam An-Nawawi Purworejo, 2018)
The library is an institution that manages the collection of written works, printed works, and / or recorded works in a professional manner with a standardized system to meet the educational, research, preservation, information, and recreation needs of the visitors. Library management is the implementation of management functions to empower management elements which include all processes from planning, organizing, mobilizing, to supervision. The nature of management is basically basically optimizing human, material, and budget contributions to achieve organizational goals. interest in reading is the tendency of the soul to encourage someone to do something about reading. Interest in reading is indicated by a strong desire to carry out reading activities. This research uses a descriptive qualitative approach. In this study, researchers chose the MTs Negeri 1 Purworejo Library. This research was conducted for one month from January 13, 2020 to February 13, 2020. To obtain and collect accurate and necessary data in this research activity, the researchers determined the respondents (actors) to be examined 1). Head master; 2). Head of Library; 3). Deputy Head of Madrasa Curriculum Section 4) Representatives of grades 7-9.The results of the study are the concept of library management in increasing students' interest in reading at MTs Negeri 1 Purworejo still in the process of development. The management used is still in the management towards a better direction, so it is expected that students can be more comfortable to visit the library so as to increase students' insight and interest in reading at MTs Negeri 1 Purworejo.